Online discussion threads as promotors of citizen democracy: Current opportunities and challenges for small- and medium-sized media organisations in Finland - Backholm Klas; Ruohonen Heini; Strandberg Kim (Nordicom Review)
This article focuses on user-generated discussion threads in journalistic online publication platforms. We investigate how journalists can apply deliberative norms to promote a democratically sustainable discussion within the threads. We also examine which opportunities and challenges journalists currently see with such threads in relation to central citizen democracy principles such as user participation and interactivity. Semistructured interviews were conducted with 18 Finnish news journalists and personnel in charge of moderation strategies. The findings show that deliberative norms are used to some degree in discussion-thread moderation, and that such norms are a key factor to promote democratically sustainable discussions in media organisations. The findings also show that threads can be useful tools for promoting citizen democracy due to their participatory features, but that several current challenges affect this, including uncivil user-generated content, limited representativeness among active users, and lacking resources to handle content in smaller media organisations. One main implication is that journalists see a risk of challenges with discussion threads outweighing benefits for democracy.